Analisis Analisis Kesalahan Mahasiswa Dalam Menyelesaikan Soal Struktur Aljabar Materi Grup Siklik Dengan Menggunakan Prosedur Newman - SL Manurung; Theresia Damanik; Shaerleen Naviry Br Kembaren; M. Arief Rizky F (Journal on Education, 2024)
This research uses a qualitative descriptive approach to describe the types and causes of student errors in solving algebraic structure questions on cyclic group material using the Newman procedure. The research subjects were 8 6th semester students who were chosen randomly. The research results showed that student errors included reading errors (12.5%), understanding the questions (37.5%), processing skills (37.5%), writing the final answer (25%) and no errors were found in the transformation. The causes of errors are inaccuracy in reading the questions, not understanding the questions, not knowing how to solve them, and not being careful in calculations. The mistake that often occurs is not writing down what is known and asked, thereby affecting the final result or conclusion. This error analysis can help identify the location of errors and become the basis for improving learning by educators.